Tax capacity in the West African economic and monetary union an assessment of tax efforts and tax gaps of WAEMU member states - Alou Adessé Dama; Anouck Daubrée; Grégoire Rota Graziosi (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The Fourth International Conference on Financing for Development, scheduled to take place in Spain from June 30 to July 3, 2025, will address and revitalize strategies for Domestic Revenue Mobilization (DRM) essential to achieving the Sustainable Development Goals (SDGs). Building on the 2015 Addis Ababa conference, which highlighted the pivotal role of national tax systems in financing sustainable development, DRM-particularly through enhanced tax revenues-has emerged as a key priority for numerous nations, spurring a series of tax reforms.
Keywords: 330; Tax; West African Economic and Monetary Union (WAEMU)